Nutritional Content of Finisher Phase Boiler Chicken Rations Containing Fermented Bean Sprouts Waste Flour - Ni Ketut Mardewi; Ni Ketut Sri Rukmini; I Gusti Ayu Dewi Seri Rejeki (Warmadewa University Press, 2019)
The ration must meet quality requirements because the provision of the quality ration is an important factor that determines the success of broiler chicken farming. Bean sprouts waste flour has the potential as one of the ingredients in broiler chicken ration and is a source of vegetable protein. Protein content in bean sprouts waste flourishes quite high, but the crude fiber content is also high so fermentation needs to be done to improve digestibility and nutritional quality. The quality of feed ingredients that form the ration greatly influences the final product made, which is ration. The purpose of this study was to determine with certainty the water content, ash content, BETN, and ME of finisher phase broiler chicken rations containing fermented bean sprouts waste flour by proximate analysis. This research was conducted using a completely randomized design (CRD) with 4 treatments and 3 replications in each treatment. The treatments applied were P0 = rations without fermented bean sprouts waste flour, P1 = rations with 3% bean sprouts waste flour, P2 = rations with 6% bean sprouts waste flour and P3 = rations with 9% Bean sprouts waste flour The variables analyzed were water content, ash content, BETN and ME ration. The results of this study indicate the use of fermented bean sprouts waste flour in finisher phase broiler chicken ration significantly (P